Quality cost accounting of products in the context of growing of the biological assets of gardening - Михальська, Віра Вікторівна (Technology audit and production reserves, 2015)
Negative influence of humanity on an environment, a high competition and openness of world markets for realization of fruits and berries require to carry out the production of high-quality goods that answers international standards and at the same time takes into account the consumer’s requirements. As a result, the creation of the quality management system at the gardening enterprises is importance and necessity. At the same time, quality cost accounting is the informative base for this system. The main aim of the article is the study of problem moments of the quality cost accounting of gardening products. The classification of quality cost accounting taking into account «total quality management conception», which worked out by Edwards Deming, and features of biological assets growing. The two groups of quality costs of gardening products are suggested and a list over for each group is brought beginning from the stage of production planning to garden product storage. The objects and methods of quality cost accounting are certain. For example, the costs that are caused to the improvement of gardening product quality and control of their indexes, subject to condition their considerable absolute sizes, to take on соsts of other operate activity by parts. That other quality are expedient to represent in composition the future period costs, with their next writing covered on costs of other operating activity at the end of every report period with the aim of avoidance market competitiveness and profitable activity. The system of sub-accounts of analytical accounting is worked out. The division «Quality costs of gardening products» that is expedient for application in practical activity of the investigated enterprises is suggested to add in the order about registration politics. By the results of research, the detailed and reasonable conclusions are done. At the further research stages of quality cost problems in gardening it is necessary to point at development of the new administrative accounting reports and perfection of the financial reporting with the aim of acceptance of reasonable and effective administrative decisions. Also, we must pay attention and develop the methodical recommendations in relation to internal control of quality costs.